Clinical application of advanced MR methods in children: points to consider. Issue 11 (27th September 2018) - Wilke, Marko; Groeschel, Samuel; Lorenzen, Anna; Rona, Sabine; Schuhmann, Martin U.; Ernemann, Ulrike; Krägeloh‐Mann, Ingeborg
Abstract: The application of both functional MRI and diffusion MR tractography prior to a neurosurgical operation is well established in adults, but less so in children, for several reasons. For this review, we have identified several aspects (task design, subject preparation, actual scanning session, data processing, interpretation of results, and decision‐making) where pediatric peculiarities should be taken into account. Further, we not only systematically identify common issues, but also provide solutions, based on our experience as well as a review of the pertinent literature. The aim is to provide the clinician as well as the imaging scientist with information that helps to plan, conduct, and interpret such a clinically‐indicated exam in a way that maximizes benefit for, and minimizes the burden on the individual child.